Pengaruh Penggunaan Alat Peraga Puzzle Terhadap Minat Belajar Peserta Didik Dalam Pembelajaran Bahasa Indonesia Di MI Muhammadiyah Ngadirejan - Siska Dian saputri; Happy Agustiani (Journal on Education, 2024)
This study aims to determine how the influence of the use of puzzle props on students' interest in learning Indonesian MI Muhammadiyah Ngadirejan. This research is a quantitative research. The research methods used are questionnaire and observation data. The sample used for this study was MI Muhammadiyah Ngadirejan students. The study was conducted using a random sampling method with a sample of 35 students. The data analysis techniques used in this study are questionnaire tests, normality, descriptive statistics, regression tests, and hypotheses. Based on the results of the regression test, a significance result of 0.008 was obtained. Ho was rejected because the significance value was less than 0.05 and the number T (2.832) was greater than the table T of 1.69389. It can be concluded that the application of Puzzle teaching tools has a great influence on students' interest in learning Indonesian subjects at MI Muhammadiyah Ngadirejan.